Stylistic Analysis of Transitivity Features in Selected Excerpts from Chimamanda Ngozi Adichie’s Purple Hibiscus (2003) - KOUTCHADE, INNOCENT SOUROU (My University, 2019)
This study explores the Transitivity features (Process Types, Participants and Circumstances) in two extracts drawn from Adichie (2003) in order to find out the salient linguistic resources which serve to encode her literary style and mind-style. It uses the Hallidayan brand of linguistics called Systemic Functional Linguistics (cf. Halliday (1971); Eggins (1994/2004); Fontaine (2013), etc.), mainly the grammar of Ideational/Experiential Meaning (otherwise known as Transitivity) to analyze the selected extracts both quantitatively and qualitatively. The findings reveal that the writer has used the six process types (material, mental, behavioral, verbal, existential and relational) at varying degrees, but the most dominant type in these extracts is material process, mainly transitive material process, the agency in these processes is predominantly marked as externally-caused and the circumstances, especially circumstances of location and manner, markedly tend to encode a typical spatio-temporal setting therein. All these features denote the writer‟s preference of/for physical and concrete depiction
Keywords: Concrete depiction; Process type; Systemic functional linguistics; Style.